Guglielmi Detachable Coil Extraction: Suction Generated by Pusher-Wire Withdrawal after Coil Detachment within an Intracranial Aneurysm - Ng, Perry P.; Halbach, Van V.; Caragine, Louis P.; Dowd, Christopher F.; Higashida, Randall T. (American Journal of Neuroradiology, 2003)
Summary: We present a case of Guglielmi detachable coil extraction into a microcatheter after coil detachment during embolization of a superior hypophyseal artery aneurysm; extraction was a result of the suction generated during pusher-wire withdrawal. Experimental simulations using many coil and microcatheter combinations were used to identify factors that contribute to the likelihood of this phenomenon.